Interactive effects of severe drought and grazing on the life history cycle of a bioindicator species. Issue 18 (1st September 2018) - Fritts, Sarah Rebecah; Grisham, Blake A.; Cox, Robert D.; Boal, Clint W.; Haukos, David A.; McDaniel, Patricia; Hagen, Christian A.; Greene, Daniel U.
Abstract: We used the lesser prairie‐chicken ( Tympanuchus pallidicinctus ), an iconic grouse species that exhibits a boom–bust life history strategy, on the Southern High Plains, USA, as a bioindicator of main and interactive effects of severe drought and grazing. This region experienced the worst drought on record in 2011. We surveyed lesser prairie‐chicken leks (i.e., communal breeding grounds) across 12 years that represented 7 years before the 2011 drought (predrought) and 4 years during and following the 2011 drought (postdrought). Grazing was annually managed with the objective of achieving ≤50% utilization of aboveground vegetation biomass. We used lek ( n  = 49) count data and covariates of weather and managed grazing to: (a) estimate long‐term lesser prairie‐chicken abundance and compare abundance predrought and postdrought; (b) examine the influence of annual and seasonal drought (modified Palmer drought index), temperature, and precipitation on long‐term lesser prairie‐chicken survival and recruitment; and (c) assess and compare the influence of grazing on lesser prairie‐chicken population predrought and postdrought. Lesser prairie‐chicken abundance was nearly seven times greater predrought than postdrought, and population declines were attributed to decreased survival and recruitment. The number of days with temperature >90th percentile had the greatest effect, particularly on recruitment. The population exhibited a substantial bust during 2011 and 2012 without a boom to recover in four postdrought years. Adaptive grazing positively influenced the population predrought, but had no effects postdrought. Results suggest that the severe drought in 2011 may have been beyond the range of environmental conditions to which lesser prairie‐chickens, and likely other species, have adapted. Land management practices, such as grazing, should remain adaptive to ensure potential negative influences to all species are avoided. Increasing habitat quantity and quality by reducing habitat loss and fragmentation likely will increase resiliency of the ecosystem and individual species. Abstract : We used the lesser prairie‐chicken ( Tympanuchus pallidicinctus ), an iconic grouse species that exhibits a boom–bust life history strategy, on the Southern High Plains, USA, as a bioindicator of main and interactive effects of severe drought and grazing. The population exhibited a substantial bust during 2011–2012, primarily through reduced recruitment due to excessive heat, without a boom to recover in four postdrought years. Adaptive grazing positively influenced the population predrought, but had no effects postdrought.